IMPLEMENTATION OF AN INTERNET OF THINGS (IOT) BASED WATER QUALITY MONITORING AND CONTROL SYSTEM FOR DAMS USING ESP 32 - amrosi (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Clean water quality is a crucial factor in supporting community health and activities, particularly in the Situbondo region, which has dam water sources of uncertain quality due to high turbidity and excessive nutrient content. Conventional water quality monitoring still relies on laboratory testing, which is time-consuming, costly, and requires limited site access. Although previous studies have developed Internet of Things (IoT)-based water quality monitoring systems, most have focused on a single platform and have not integrated a real-time notification system that is easily accessible to users. The gap in this research lies in the lack of a water quality monitoring system that combines a visualization platform, automatic validation, and instant notification in a single integrated architecture. This research presents a novelty in the form of the integration of ESP32 and DHT22 sensors. This sensor was transformed into a water turbidity sensor using the Blynk platform as a data visualization system and Telegram as a real-time notification medium. The research method used was a prototype method, which included stages of listening to customers, building/revising mock-ups, and mock-up trials by customers. The results showed that this system is capable of monitoring water quality in real-time, transmitting sensor data stably via a Wi-Fi network, and providing automatic notifications when water parameters exceed specified thresholds. This system has proven responsive, accurate, and effective in reducing the need for manual monitoring, thus potentially supporting sustainable water quality management.